طريقة الترجمة الشفوية: The Method of Oral Interpretation - Chamdar Nur; Andi Abdul Hamzah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This article, entitled “The Interpreting Method,” aims to highlight the role of oral interpreting as a pedagogical approach in teaching Arabic as a foreign language within Islamic educational institutions, rather than viewing it merely as a tool for transferring messages between two languages. The study departs from the observation that Arabic curricula are still largely grammar and text oriented, with insufficient attention given to oral communicative skills, particularly interpreting. It seeks to identify the main principles of the interpreting method (fidelity of meaning, speed with accuracy, and contextual–communicative orientation), to outline its key techniques (simultaneous, consecutive, whispered interpreting, and keyword-based interpreting), to analyse the concept of equivalence in its semantic, functional, cultural, and pragmatic dimensions, and to show how these elements can be mobilized to develop learners’ communicative competence. A qualitative descriptive design was adopted, combining classroom observations in selected Islamic institutions, a systematic review of relevant literature, and semi-structured interviews with teachers of Arabic as a foreign language, followed by thematic analysis of the data. The findings indicate that structured training in interpreting enhances listening and speaking skills, rapid cognitive processing, and intercultural sensitivity, and functions as a bridge between receptive and productive abilities while supporting task-based learning in the classroom. The study contributes by conceptualizing interpreting as an integrated teaching method in Arabic curricula at Islamic institutions and by proposing practical avenues for its inclusion in course design and teacher-training programmes.